The impacts of Acquisition on the Bidder's Cash Flow Structure (The case of PT Central Sentosa Finance acquisition by PT Bank Central Asia) - Fitriningrun, Andriati; Pulungan, Andrey Hasiholan; Wijayanto, Gilang Fajar (Jurnal Manajemen, 2020)
The purpose of this study is to examine the impact of Merger and Acquisition (M&A) wave on constructing the capital structure. The conflict of government policies to assist the Small Medium Enterprises (SMEs) is in conflict with the other regulation which requires banks to meet the minimum Net Performing Loan (NPIL). This situation encourages the emergence of M&A wave in Indonesia. Numbers of banks do M&A as the option to accommodate the government regulations. Using the case of PT Central Sentosa Finance (CSF) acquisition by PT Bank Central Asia (BCA), this study examines the M&A impacts on the bidder's capital structure when the acquisition due to the wave and government policy. The quantitative method is used to examine the impact of M&A on the company's capital structure focusing the 2014 acquisition. The study contributes to the accounting in the area of transparency and capital issues. The statistical results show that the potential policies conflict drives the company to prioritize the selection of funding.